Analysis of human resources governance system in the framework of increasing the business of PT. Rumah Sakit Mata Pekanbaru - Efhandi, Muhammad Hanif Imaduddin (International Journal Labs, 2024)
The Pekanbaru Eye Hospital Eye Center (PBEC) is one of the Eye Hospitals that is quite famous in the city of PekanBaru in particular and in Riau Province in general. It is a tertiary hospital located in the northern part of Indonesia. The eye hospital industry has a great impact on the quality of eye health services. This study aims to investigate how HR at PBEC Eye Hospital is managed to achieve high productivity and positive outcomes, such as consumer satisfaction and hospital business performance, positing that effective HR governance leads to better results, while poor governance has negative impacts. This research has two primary objectives: to fulfill a graduation requirement at Bina Nusantara University, Jakarta, and to offer insights to eye hospital managers on the role of Human Resource Governance in hospital development, particularly at the eye hospital. The findings of this study will provide an in-depth understanding of how HR governance can support the progress of the hospital's business, as well as strategic steps to improve HR governance that have the potential to improve hospital performance. The suggestions submitted include improving the process and quality of HR governance through improving SOPs, training, consulting, and technology.